Caracterização do transcriptoma e da produção embrionária de espermatozóides sexados por citometria de fluxo ou por gradiente de densidade - Santos, William Jardim de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The procedures for sexing by flow cytometry guarantee the accuracy of 85%, but cause damage in sperm viability leading to lower pregnancy rate after 90 days of pregnancy. The objectives of this study were: 1) to characterize differential gene expression in transcriptome of spermatozoa frozen by conventional method, sexed by density gradient centrifugation, by flow cytometry. 2) Compare blastocyst and cleavageratesproduced in vitro by conventional semen sexed by flow cytometry and by density gradient centrifugation. The experimental groups for semen and embryos were: 1) control group: conventional semen subjected to PercollTM gradient of 45/90% and their embryos produced with this semen, 2) gradientgroup: centrifugation in density gradient and their embryos produced with this semen, 3) cytometry group: semen sexed by flow cytometer, subjected to PercollTMmini gradient 45/90% and their embryos produced with this semen. Total RNA was extracted from sperm (20 x 10 6 cells) and it was possible to extract 400 ngRNA/ 20x10 6 cells/animal or it means, 20 fg of RNA per spermatozoa. However cDNA libraries were not built, probably due a high RNA degradation. The cumulus oocyte complexes (COCs) were classified as grade 1, aspirated from antral follicles with 3-8 mm in diameter, ovariesfromslaughterhouse were used and matured for 18 hours in an incubator at 38.5°C, 100% humidity and atmosphere of 5% of CO2 in air. The matured oocytes are going to be placed in contact with the prepared spermatozoa for fertilization and incubated for 20 hours in 5% CO2 at a temperature of 38.5 °C. Presumptive zygotes are going to be washed three times in SOF (half synthetic oviduct fluid) without FBS and without glucose, cultivated and transferred to plates with four wells containing 500 ul of the same medium used for washing zygotes after fertilization. Embryonic development was evaluated 7-8 days after fertilization. The cleavage and blastocysts rates were ...

Os procedimentos durante a sexagem pelo citômetro de fluxo garantem a acuidade de 85%, mas causam danos na viabilidade espermática que levam a baixa taxa de prenhez após os 90 dias. Os objetivos dessa Dissertação foram: 1) caracterizar a expressão gênica diferencial em transcriptoma de espermatozoides congelados pelo método convencional, sexados por centrifugação em gradiente de densidade ou sexados por citometria de fluxo; 2) comparar as taxas de clivagem e de blastocistos produzidos in vitro de bovinos utilizando sêmen convencional, sexado por citometria de fluxo ou por centrifugação em gradiente de densidade. Os grupos experimentais para sêmen e embriões foram: 1) grupo controle: sêmen convencional submetido ao gradiente de PercollTM 45/90% e respectivos embriões produzidos com esse sêmen; 2) grupo gradiente: centrifugação em gradiente de densidade e respectivos embriões produzidos com esse sêmen; 3) grupo citometria: sêmen sexado pelo citometro de fluxo, submetido ao mini gradiente de PercollTM 45/90% e respectivos embriões produzidos com esse sêmen. O RNA total foi extraído dos espermatozoides (20 x 10 6 células) obtendo-se 400 ng RNA/ 20 x 10 6 células/ animal, ou seja, 20 fg RNA por espermatozoide. Entretanto, não foi posível a construção da biblioteca de cDNA, provavelmente, devido ao alto grau de degradação do RNA. Os Complexos cumulus oócito (COCs) classificados como graus 1, foram aspirados de folículos antrais de 3 a 8 mm de diâmetro a partir de ovários de abatedouros e maturados durante 18 horas em estufa a 38,5°C, 100% de umidade e atmosfera de 5% de CO2 em ar. Os oócitos maturados serão colocados em contato com os espermatozoides previamente preparados para fecundação e incubados por 20 horas em 5% de CO2, na temperatura de 38,5°C. Os prováveis zigotos serão lavados por três vezes em meio SOF (meio sintético de fluido de oviduto) sem SFB e sem glicose e cultivados e transferidos...
Keywords: Bovino; Reprodução animal; Espermatozoides; Bovino - Sexagem; Expressão gênica; Sexing